A Threshold QuickDASH Score for Estimating a Diagnosis of Major Depression in Patients With Fingertip Injuries in the American and Dutch Population. (June 2023) - Oflazoglu, Kamilcan; Verheul, Elfi M.; Pong, Taylor M.; Ritt, Marco J. F. P.; Rakhorst, Hinne; Chen, Neal C.
Background: The aim was to determine the threshold Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) score that estimates a diagnosis of major depression in patients with fingertip injuries in American and Dutch patients. Methods: In this observational cross-sectional study, 112 patients with a recent fingertip injury measured symptoms of depression with the Patient Health Questionnaire and upper extremity disability with the QuickDASH. Results: In the US cohort, 8 of 56 patients had an estimated diagnosis of major depression. A threshold value of QuickDASH of 50 showed a sensitivity of 88% and a specificity of 81%, with a negative predicting value (NPV) of 95% for an estimated diagnosis of major depression. In the Dutch cohort, 7 of 56 patients had an estimated diagnosis of major depression. The same threshold score of 50 had a sensitivity of 71%, a specificity of 63%, and an NPV of 94%. Conclusions: We have found a correlation between experienced loss of function and an estimated diagnosis of major depression in patients with a fingertip injury. Referral to the primary care physician for further evaluation of depression in these patients is advised.